Penetapan Isbat Wakaf Nomor 281/PDT.P/2011/Pa.CLG Dalam Perspektif Hukum Progresif - Veri Triyono (Falah: Jurnal Hukum Ekonomi Syariah, 2021)
After the determination of the Isbat waqf case with number 281/Pdt.P/2011/Pa.Clg. by the Cilegon Religious Court is very interesting to study and make scientific research. This is because the determination of the isbat waqf case is still very rare and this gives rise to different legal interpretations regarding the provisions of isbat waqf in the legal system in Indonesia and about the absolute authority of the Religious Courts. There have been many scientific works or researches that have examined the determination of the Cilegon Religious Court with a normative legal analysis approach. Therefore, in this study, the authors take a different approach, namely the formulation of the problem, namely: How is the analysis of the Cilegon Religious Court Decision Number 281/Pdt.P/2011/Pa.Clg regarding the Isbat Waqf case in a progressive legal perspective? The research method used in the research is library research or library research with qualitative research. Legal research with a normative juridical approach by referring to the legal norms contained in the legislation and court decisions as well as Islamic legal norms. The results of research on the determination of the number: 281/Pdt.P/2011/Pa.Clg. In 2011 by the Cilegon Religious Court in a progressive legal perspective, namely: decisions made by Cilegon Religious Court judges as an effort to break the ice in law. in accordance with Article 4 of Law No. 48/2009. The judge's consideration trying to interpret the authority to grant the determination of waqf isbat away from the legal text and approaching the benefits for humans or the applicant applicant has illustrated how progressive law is present in Decision Number 281/Pdt.P/2011/Pa.Clg